The Development of Case Management Model in Patients with Acute Myocardial Infarction based on Muslim Context, Naradhiwasrajanagarindra Hospital - Sahmaae, Narisa; Phutkeaw, Saowalak; Khanbo, Kanokrat (Princess of Naradhiwas University Journal, 2022)
This research and development aimed to develop a case management model for patients with acute myocardial infarction and to study its outcomes in the Muslim context at Naradhiwasrajanagarindra Hospital. The participants were: 1) 34 registered nurses at the emergency unit, cardiac care unit, male medicine ward 1, and female medicine ward and 2) 30 patients with STEMI who received the thrombolytic drugs at Naradhiwasrajanagarindra Hospital. The researcher divided the operation methods as follows: 1) the situation analysis phase, 2) the execution phase, and 3) the evaluation of the data analysis phase. In phase 1, the researchers analyzed the data obtained from the interview and focus group using content analysis. The data were collected from Phase 2 and 3. Research tools consisted of multidisciplinary team role guide, Clinical Pathway, flip-plate to educate acute myocardial infarction, general information questionnaire, the satisfaction assessment form for the use of care guidelines (Cronbach alpha coefficient = 0.81), and nurses’ knowledge test (Kuder-Richardson = 0.85). Data were analyzed using descriptive statistics, frequency distribution, percentage, mean, standard deviation, and paired sample t-test. The results of this study revealed that Naradhiwasrajanagarindra Hospital has created a model of care by case managers for patients with acute myocardial infarction in the Muslim context, which has resulted in a systematic approach to the improvement of patient care. Moreover, nurses have gained more confidence and competence in patient care. Knowledge scores after training were statistically significant (p< 0.001) and significantly different from those before the training (before training; mean=10.62, SD=2.64 and after training; mean=13.29, SD=1.71) The satisfaction of following the guidelines was at a high (mean = 4.25). For patients with acute myocardial infarction, there was a high level of satisfaction with using the care guidelines (mean = 4.15). Additionally, the outcomes of the nursing care according to the indicators of patients with acute myocardial infarction were ameliorated to provide patients with standardized care.